PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL DI PENGADILAN NEGERI PEKANBARU TERHADAP PEMENUHAN HAK PEKERJA PADA SENGKETA PEMUTUSAN HUBUNGAN KERJA - Dania Sabilah Farina; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Law Number 13 Year 2003 concerning Manpower regulates layoffs. As for the rights incurred after the termination of employment which were incurred after the termination of employment received by workers / laborers in the form of rights to money / wages which include process wages, severance pay, awards and compensation compensation. Settlement of PHK Disputes is the authority of the Industrial Relations Court at the local District Court. The purpose of this thesis is; First, to find out the decision of the industrial relations court judge in Pekanbaru District Court number: 103 / Pdt.sus-PHI / 2018 / PN.Pbr is in accordance with the theory of justice; Second, to find out the industrial relations court decision in Pekanbaru District Court number: 103 / Pdt.sus-PHI / 2018 / PN.Pbr has provided legal certainty.This type of research is classified in the type of Normative Law research, namely legal research conducted by examining library materials or secondary data. The study was conducted at the Pekanbaru District Court. The data source used is secondary data and is supported by primary data using interview techniques. Data collection techniques used are from the study of documents or library materials, then the data are analyzed qualitatively obtained from secondary data.Based on the research results, there are 2 main things that can be concluded, first, the decision of the industrial relations court in the Pekanbaru District Court Number: 103 / Pdt.sus-PHI / 2018 / PN.Pbr, the judges have given justice to the parties, especially the workers , because the plaintiff's initial lawsuit requested that the employment relationship be broken since October 31, 2018 and was granted by the judge, so that the workers' rights only until October 31, 2018 included process wage rights which were also requested to be granted in the lawsuit, so article 155 of Law Number 13 of 2003 concerning Manpower cannot be a guideline for judges. Second, the Panel of Judges has decided that the decision has provided legal certainty to the parties, as explained by Hans Kelsen and Soedikno Mertokusumo, that legal certainty is a written law. The initial claim to terminate the employment relationship since 31 October 2018 was granted by the panel of judges, so that normative rights and other rights including the right to process wages were also requested by the plaintiff in his claim only until 31 October 2018. The author's suggestion, the plaintiff should have asked for a termination of employment relations until a court decision has permanent legal force, so that the provisions in Article 155 Paragraph 2 of Law Number 13 of 2003 concerning Manpower and the Decision of the Constitutional Court Number 37 / PUU-IX / 2011 concerning Application for Judicial Review of Law Number 13 of 2003 concerning Manpower and Article 16 paragraph 1 of the Decree of the Minister of Manpower Number Kep.150 / Men / 2000 of 2000 can be a guideline for judges to grant process fees.Keywords: Layoffs by Workers - PHI Decisions - Process Wages.